Yurisometry as an Alternative Approach in Normative Legal Research in Indonesia: A Conceptual Study - Budiana, Budiana; Maulana, Galih Afif Sylva; Anugrah, Dicky; Dani, Mohamad; Sondakh, Eduard (Indonesian Journal of Law and Economics Review, 2026)
General Background: Legal scholarship in Indonesia is predominantly shaped by normative legal research, which examines legislation, legal principles, and legal doctrines as the foundation of juridical reasoning. Specific Background: While this approach contributes significantly to legal certainty and systematic legal analysis, judicial practice frequently reveals variations in the interpretation and application of legal norms in court decisions. Knowledge Gap: Normative legal research alone often encounters limitations in explaining recurring patterns, interpretative tendencies, and inconsistencies within judicial rulings, and the conceptual discourse on integrating jurimetrics into normative legal methodology in Indonesia remains limited. Aims: This study examines jurimetrics as an alternative complementary approach to normative legal research in Indonesia through a conceptual legal study. Results: The analysis indicates that jurimetrics, which utilizes legal data such as court decisions to identify patterns, trends, and levels of consistency in legal interpretation, can function as an analytical instrument supporting normative reasoning without replacing doctrinal analysis. Novelty: The study conceptually positions jurimetrics within the methodological framework of normative legal research as a bridge connecting legal norms with judicial practice. Implications: The integration of jurimetrics offers methodological relevance for developing normative legal research that remains doctrinal and prescriptive while becoming more responsive to the dynamics of judicial decision-making in Indonesia. Highlights: Data-oriented examination of court rulings reveals recurring reasoning patterns and interpretative tendencies in adjudication. Analytical integration links doctrinal examination of legal norms with observable judicial decision patterns. Conceptual framework situates jurimetrics as a methodological complement within Indonesian legal scholarship. Keywords: Normative Law, Complementary, Judiciary, Legal Principles, Jurimetrics